Basophil activation test: Implementation and standardization between systems and between instruments. Issue 3 (9th March 2017) - Depince-Berger, Anne‐Emmanuelle; Sidi‐Yahya, Khaled; Jeraiby, Mohammed; Lambert, Claude
Abstract: The basophil activation test (BAT) is a good ex vivo alternative for measuring hypersensitivity to an allergen in sensitized patients but still lacks standardization. In this present study, we have implemented one of the systems and proposed inter‐systems, inter‐instrument standardization. Our method for basophil activation and labeling on whole blood: EDTA in one step using BasoflowEx ® and FlowCast ® . Setup on Navios and fluorescence targets converted to set up FACSCanto™ instrument. Our results: 1) A CD203c/CD63 (BasoflowEx) method was adapted for EDTA samples and simplified. 2) Final washing and concentration and use of time parameter help acquiring as many basophils as possible, spare acquisition time and noise. 3) The modified method was validated according to ISO15189 with a precision at 5.1% RCV, linearity between 1 and 1/8 of anti‐IgE stimulation. Results were very close with CCR3/CD63 system (FlowCast). 4) Standardization, between systems and even between instruments. Mean Fluorescence Intensity targets are proposed using standard beads (Cytocal ® ) middle peak: FITC = 19.4; PE = 28.8 on Navios ® corresponding to FITC = 4, 966; PE = 7, 373 for FACSCanto. Data analyzed on common software (Kaluza ® ) were very closely correlated. 5) Co‐labeling of B cells (CD20+) gives the possibility to monitor a significant drop of basophils under stimulation that could explain some underestimation in case of strong hypersensitivity. In conclusion, BAT would strongly benefit from easy implementation [EDTA, one step stimulation/labeling, wash, full sample analysis over time parameter, B cell relative basophil count] and standardization of instrument settings on MFI targets whatever system or instrument is used. © 2017 International Society for Advancement of Cytometry